ChemInform Abstract: Palladium‐Catalyzed Construction of Amidines from Arylboronic Acids under Oxidative Conditions. Issue 43 (7th October 2016) - Zhu, Fengxiang; Li, Yahui; Wang, Zechao; Orru, Romano V. A.; Maes, Bert U. W.; Wu, Xiao‐Feng
Abstract: The multicomponent approach to the amidine class tolerates various functional groups and leads to generally moderate to good yields.